Results- driven staff development - Sparks, Dennis; Hirsh, Stephanie (Utah : The Video Journal of Education, 1996)
This issue bring the program which help educators experience a paradigm shift necessary to implement quality training that will improve student achivement
Program 1 : A paradigm shift: staff development for improved learning Program 2 : National staff development council standards for staff development (parts one and two)
Volume 6, Issue4